A New Model for Reassignment of Tasks to Available Employees in Iraq's Firms. (8th April 2020) - Ibrahim Alsaad, Dhurgam Kalel; Ghanbari, Reza; Sohrabi, Ali Akbar; Ghorbani Moghadam, Khatere
Abstract : Generalized assignment problem (GAP) is a well-known problem in the combinatorial optimization. This problem is a specific form of assignment problem (AP) when the employees can carry out more than one task simultaneously or each work can be assigned to more than one employee. In this paper, a new model is proposed for reassigning tasks on the available employees of Iraq companies when at least one of the jobholders is absent. Likewise, the returning workers from long holidays assumption are incorporated. Finally, a heuristic algorithm for solving reassignment tasks on laborers is introduced.